IMPLEMENTASI SUPERVISI AKADEMIK DAN DAMPAKNYA TERHADAP MUTU PEMBELAJARAN DI SMK MUHAMMADIYAH 3 TERPADU PEKANBARU - Cindy Alia Tasya; Jenni Akmal; Nurhalimah Nurhalimah (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This study aims to describe the implementation of academic supervision and its impact on the quality of learning at SMK Muhammadiyah 3 Terpadu Pekanbaru. The research employed a qualitative approach with a descriptive design. The research participants included the principal, the vice principal for curriculum affairs, and teachers. Data were collected through interviews, observations, and documentation. Data analysis was conducted through data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings indicate that academic supervision at SMK Muhammadiyah 3 Terpadu Pekanbaru is implemented systematically through the stages of planning, implementation, and follow-up. The planning stage involves structured scheduling, the formation of a supervision team, and the use of supervision instruments. The implementation stage is carried out through classroom observations using an objective and collaborative approach. Follow-up activities include reflective discussions, coaching, and professional development training for teachers. Academic supervision has a positive impact on learning quality, as reflected in improvements in lesson planning and instructional practices, enhanced teachers’ pedagogical competence, and the development of a culture of quality learning within the school. Thus, academic supervision plays a strategic role in supporting sustainable improvement in learning quality.